SISTEM PENGENDALIAN INTERNAL DALAM MENINGKATKAN EFISIENSI PERSEDIAAN BARANG DAGANG PT. FORBES INDONESIACABANG MEDAN - Hernawaty (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2019)
This research aims is to analyze internal control of inventory carried out by PT. Forbes Indonesia Medan Branch, then to prove whether it have the impact to and can improve the efficiency of merchandise inventory on the company. This company engaged in the sale of electronic equipment for household appliances such as vacuum cleaners, water purifiers, washing machines and so on. The problem faced is the distributionconstraints from factories in Switzerland such as cost issues, damage in shipping, availability of goods and diversity of products sold that require good inventory control. This research using descriptive technique with a qualitative approach. Data collection techniques in this study are using interviews and documentation, which the data used are primary and secondary data. The results of the research have been obtained thatthe internal control of the company has been quite effective in increasing the efficiency of its merchandise inventory, where controll procedures are in accordance with the elements of good control according to the COSO framework. The five elements are already good but there are still deficiencies in the section specifically dealing with internal audit where the role and function of the internal audit has been held by BBM (Branch Business Manager) at the company